Effects of coffee processing residues on anaerobic microorganisms and corresponding digestion performance - Rojas Sossa, Juan Pablo (2017)
The objective of this study was to delineate the effects of different coffee processing residues on the anaerobic microbes and corresponding digestion performance. The results elucidated that mucilage-rich feed enhanced the accumulation of methanogens, which consequently led to better digestion performance of biogas production. Fifty percent more methane and up to 3 times more net energy (heat and electricity) output were achieved by the digestion of the mucilage-rich feed (M3). The microbial community and statistical analyses further elucidated that different residues in the feed had significant impact on microbial distribution and correspondingly influenced the digestion performance.